Employer Image in Lithuania: Economical Context - Marčinskas, Albinas; Paulauskaitė, Loreta; Drūteikienė, Greta (Ekonomika, 2007)
The ultimate goal of this article is to examine image of attractive employer in Lithuania and to identify characteristics affecting it. Employer attractiveness towards potential employees becomes more and more important considering the mobility of today’s labourmarket. Objectives of this article are to analyse the concept and features of attractive employer image; to identify Lithuanian companies, which are the most and the least attractive as employers; to evaluate the importance of certain characteristics fur attractive employer image and to indicate those characteristics, which are the most fu:queotly assigned to attractive employers. Should the goal and objectives be reached, there was theoretical analysis and representative survey of Lithuanian residents conducted. Analysis of the literature resulted in the conclusion that image of an employer is the perception of organization, as the employer, of existing and potential employees or society in general. Development of a company, as attractive employer, image is an opportunity to extend positively beyond the competitive environment. Not individual characteristics but rather a complex set of their interrelations make, employer attractive. Survey showed that in Lithuania image of attractive employer is affected by ability to have an interesting work, worklife balance as well as great atmosphere at work. Good management and ability to be valued, as an employee, are not less important preconditions for employer attractiveness. Having examined survey fin· dings there is a conclusion made that today even the most attractive employers do not take a sufficient care of their own image and potential employees lack information to get one or the other opinion on employer attractiveness. Besides that, expectations of potential employees are not met sufficiently as far as importance of their needs for the work is concerned. This survey is valuable both for theoretical and practical purposes. It could be the occa.ion for tb. further academic studies of attractive employer image. Survey results could be used as a representative benchmark fur the further employer attractiveness monitoring in Lithuania. It also could be comparable with similar surveys in particular groups.